Partisipasi Komite Sekolah Dalam Meningkatkan Mutu Sekolah - Agus Suryana (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
This study aims to describe the role and participation of school committees in realizing quality schools. This research is a library research and content analysis (content analysis). This study produced the following findings: 1. Role of Advisory. In carrying out this role, the school committee has the function of providing input and recommendations to education units regarding: (1) educational policies and programs (2). School Revenue and Expenditure Budget Plan (RAPBS), (3). educational unit performance criteria (4). educational staff criteria (5). criteria for educational facilities (6). other matters related to education. 2. Supporting Role (Supporting). This supporting role includes the function of the school committee to do the following: (1). encourage parents and the community to participate in education (2). raise public funds in the framework of financing (3). encourage the growth of public attention and commitment to the implementation of quality education. 3. Controlling Role (Controlling). This controlling role includes the efforts of the school committee in the following: (1). evaluate and supervise program policies, implementation, and educational outputs. 4. Role of Mediator. This mediator role enables the school committee to carry out the following functions: (1). collaborate with the community (2). accommodate and analyze aspirations, ideas, demands, and various educational needs put forward by the community. Key words: participation, quality, community, school committee